Microextraction-Based Techniques for the Determination of Beta-Blockers in Biological Fluids: A Review - Styliani Nisyriou; Constantinos K. Zacharis (Separations)
Sample preparation is a critical step in the analytical process. Apart from the traditional sample cleanup approaches, microextraction-based techniques have attracted much attention in recent years and especially from researchers working in the analysis of beta-blockers. Developing sensitive and selective analytical methods is essential for detecting these compounds in complex matrices. The present review aims to provide an overview of microextraction-based analytical techniques for the determination of beta-blockers in biological samples, covering a time frame of the last decade. Detailed information on materials/coatings and instrumental configurations are provided.